2001
DOI: 10.1029/1999pa000493
|View full text |Cite
|
Sign up to set email alerts
|

Glacial sea surface temperatures in the subtropical North Pacific: A comparison of U37k′, δ18O, and foraminiferal assemblage temperature estimates

Abstract: It is important to determine the true nature of glacial-interglacial variations in subtropical North Pacific SSTs. Knowledge of climate sensitivity in the subtropics is essential for understanding the processes that drive climate variability and for predicting future climate change [e.g., Manabe and Broccoli, 1985a]. The attainment of such knowledge requires that the general utility and limitations of the approaches used to reconstruct past SSTs be better understood. As a step toward these goals, we are studyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…This is due to the very low sedimentation rates that are inherent to oceanic areas distant from coastal zones that drastically limit the possibilities of obtaining SST data with a reasonable resolution for Holocene SST reconstructions. Few available records surrounding Hawaii (based on alkenones (Lee et al, 2001)) and the Azorean archipelagos (based on Mg/Ca (Repschlä ger et al, 2009)), however, seem to confirm the hypothesis we have suggested for low-latitude SST responses to seasonal insolation changes.…”
Section: Perspectives To Further Improve the Understanding Of Sst Promentioning
confidence: 44%
“…This is due to the very low sedimentation rates that are inherent to oceanic areas distant from coastal zones that drastically limit the possibilities of obtaining SST data with a reasonable resolution for Holocene SST reconstructions. Few available records surrounding Hawaii (based on alkenones (Lee et al, 2001)) and the Azorean archipelagos (based on Mg/Ca (Repschlä ger et al, 2009)), however, seem to confirm the hypothesis we have suggested for low-latitude SST responses to seasonal insolation changes.…”
Section: Perspectives To Further Improve the Understanding Of Sst Promentioning
confidence: 44%
“…3) of our glacial chronology with the pollenbased record of temperature and precipitation from O'ahu (Hotchkiss and Juvik, 1999) and the alkenone-based SST record from the subtropical North Pacific (Lee and Slowey, 1999;Lee et al, 2001), shows that the two Makanaka glaciations were associated with large changes of temperature or precipitation (but not necessarily both!). At sea level, assuming our 36 Cl ages are accurate, the Older Makanaka climate was colder than today by $38C and as wet as today.…”
Section: Climatic Inferences From Makanaka Ice Capsmentioning
confidence: 99%
“…At least one additional palaeoclimatic record is necessary for a unique solution because ELA depends on both temperature and precipitation. We used two: a pollen-derived temperature record from a lowelevation (463 m) site on O'ahu (Hotchkiss and Juvik, 1999) and an alkenone-based SST record from the subtropical North Pacific (Lee and Slowey, 1999;Lee et al, 2001). During our analysis, it was necessary to transfer these low-elevation temperatures to the elevation of the Makanaka moraines.…”
Section: Climatic Inferences From Makanaka Ice Capsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was once thought to be true of the tropics, but widespread observational and modelling evidence have suggested that the glacial tropical oceans were 1-2°C cooler than today (e.g. Lee et al, 2001;Kitoh et al, 2001). This cooling may be due to the decrease in moisture in the free troposphere that accompanied global cooling during the last glacial period (Seager et al, 2000).…”
Section: Glacial To Interglacial Atmospheric Circulation Change and Imentioning
confidence: 99%